A.SAIDOV, D. YAXYOYEVA INGLIZCHA-O‘ZBEKCHA-RUSCHA SOLIQ VA IQTISODIYOT ATAMALARI LUG‘ATINING LINGVISTIK TAHLILI - Ruzimov, Sh.S. (SCIENCE and SOCIETY, 2023)
In the article compiling principles of the English-Uzbek-Russian dictionary of tax and economic terms by A. Saidov, D. Yakhayoyeva were linguistically analyzed and recommendations aimed at its improvement were presented, showing its achievements and shortcomings with examples.